First Report of Sweet Potato Virus E(SPVE) Infecting Sweet Potato in China - Tang, Wei (Plant disease, 2024)
Sweet potato (Ipomoea batatas [L.] Lam.) is a versatile crop, cultivated in the subtropical and tropical areas, as food, fodder, and industrial raw material crop. In China, sweet potato has been used as a health-care food in recent years, as it contains a wide range of nutrients and xenobiotic phytochemicals. However, viral diseases are major constraint for the sweet potato yield and quality, especially the seed production and quality. Over 30 species of viruses infect sweet potato worldwide (Clark et al. 2012). More recently, a few new viruses infected sweet potato were identified, such as sweet potato virus E (SPVE), which was reported in Korea(Jo et al. 2020). In May 2022, a sweet potato sample (JSXZ1) with virus-like symptom, such as mosaic and vein clearing were collected from sweet potato germplasm Xuzhou resource nursery, Jiangsu Province, China (N34˚16', E117˚18') (Fig. S1A). To investigate the virus disease, the sample JSXZ1 showing the typical symptoms of disease was prepared for Small-RNA (sRNA) deep-sequencing. The sRNA library was constructed using TruSeq™ Small RNA Sample Prep Kits (Illumina, San Diego, USA) and sequenced using the Illumine Hiseq 2500 platform by LC-Bop Technologies (Hangzhou) CO., LTD. The sample was sequenced to obtain 26, 358, 439 raw reads and 22, 969, 139 clean reads after quality control trimming and analysis. The Velvet 1.0.5 software was used to de novo assemble the clean reads (18 to 28 nt) into larger contigs, which were then compared with the nucleotide sequences in the National Center for Biotechnology Information (NCBI) database using the BLASTn algorithm. Viruses found in the sample were sweet potato latent virus (SPLV), sweet potato feathery mottle virus (SPFMV), sweet potato chlorotic stunt virus (SPCSV), sweet potato badnavirus A (SPBV-A) and sweet potato badnavirus B (SPBV-B). Surprisingly, besides the viruses listed above, 28 contigs matched sequences of SPVE isolate GS (MH388502). To verify the result, total RNA was extracted from the sample JSXZ1 and from other leave samples (JSXZ2-JSXZ5) that contained SPFMV, SPVC, SPLV, SPVG respectively stored in lab using FastPure Universal Plant Total RNA Isolation Kit (Vazyme Biotech Co., LTD, Nanjing, China). cDNA was synthesized using random primer (hexadeoxyribonucleotide mixture; pd(N)6). The cDNA serves as template in PCR using a newly designed primer pairs based on SPVE p1 gene (SPVE-F: 5'- TCACCAAAAAGAATGCTACAAC-3'/SPVE-R: 5'-GAAATCCTCCCACTCTCCATA-3'). An expected ~500-bp PCR fragment was obtained in JSXZ1, while none of the fragment was obtained from JSXZ2-JSXZ5 (Fig. S1B). The PCR fragment was cloned into pMD18-T vector (Takara Bio Inc., Beijing, China) and plasmid DNA from transformed Escherichia coli DH5α cell (n=3) were commercially sequenced by Sangon Biotech (Shanghai) Co., Ltd. The sequences of the three fragment clones we obtained were 100% identical when compared. A BLASTN analysis of the sequences revealed that they are specific to SPVE and shared 98.62% nucleotide identity to SPVE GS isolate (MH388502) and one sequence was submitted to GenBank (Accession number OQ948331). To determine the occurrence of SPVE in infected sweet potato plants, a total of 37 leaves samples with viral symptom collected from Shandong Province (n=6) and Jiangsu Province (n=31) were indexed by RT-PCR as described before. Only 9 (24.3%) out of 37 from Shandong (n=1) and Jiangsu (n=8) were positive to SPVE respectively. In addition, five additional viruses (SPFMV, SPVC, SPVG, SPLV, SPCSV) were detected among these 37 samples and always in a mixed infection of two or more viruses. To our knowledge, this is the first report of SPVE infecting sweet potato in China. Sweet potato is an important crop in China and other countries (Zhang et al. 2023). China is the largest sweet potato producer all over the world. In addition, as sweet potato is produced through the vegetative propagation mode, thus, more attention should be paid to detection and monitoring of occurrence of SPVE in China